STRUKTUR MODAL PERUSAHAAN PROPERTI DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Mufidah, Ana (BISMA: Jurnal Bisnis dan Manajemen, 2012)
This research analyzes capital structure of Property Company andseveral factors that influence it on go public property. Several factors thatinfluence capital structure in this research are interest rates, exchange rates andtrading volume of property stock only. Population of this research are go publicproperty companies at Indonesia Stock Exchange, they are 49 companies researchsample has been 36 companies, sample determination considers purposivesampling while research data analysis utilizes. Data analyze in this research isregresion analysis. The results show several finding, that all variable havesignificance influence to capital structure. While partial analysis only the exchangerates have significance to capital structure.